ACCOUNTING AND BUDGETING. - Theiss, Edwin L. (The Accounting Review, 1935)
Abstract Accounting and teachers of accounting have been observing with considerable interest the steady development of business budgeting, especially during the past fifteen years. To many accountants this procedure seemed to be a misuse of accounting data and any such professed forecasting of business operations appeared to be unreliable, if not altogether impossible. As time went on, however, budgeting was thoroughly tried out and tested by management. Many experiments were made. Budgetary methods were studied. Cost accountants were open-minded and contributed generously to the development of its technique and procedures. Executives and financial accountants also tried their hand at the preparation of budgetary estimates. Cost accountants, like financial accountants, aim to interpret their own records. Cost accountants are now performing an increasingly large amount of the interpretation function of accounting, for the purpose of giving management promptly informational data on current operations. Standard costs and standardized revenues cannot be ascertained without interpreting fully the accounting records of past and present performance.